Hands-on geospatial analysis with R and QGIS : a beginner's guide to manipulating, managing, and analyzing spatial data using R and QGIS 3.2.2 /: a beginner's guide to manipulating, managing, and analyzing spatial data using R and QGIS 3.2.2. (2018) - Islam, Shammunul
No abstract available